PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT BPR KARTASURA SARIBUMI CABANG MASARAN - Juni Trisnowati (Universitas Sahid Surakarta, 2013)
This study analyzesthe influence ofmotivationand disciplineto theperformance of employeesof PTBPRKartasuraSaribumiCabang Masaran. The problemsareformulatedis:is there asignificant relationship betweenmotivationand disciplineto employee performanceeither partially orsimultaneously. The hypothesis is